Pengaruh Corporate Sosial Responsibility Dan Efektivitas Aset Terhadap Return Saham: Peran Moderasi Kebijakan Dividen - Wibowo, Francisco; Agustina, Risti; Anisa, Anisa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and asset effectiveness on stock returns, with dividend policy positioned as a moderating variable. A quantitative method is employed to explain the relationship among variables using secondary data derived from annual reports, sustainability reports, and stock market information of energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The research utilizes panel data regression with Moderated Regression Analysis (MRA) to evaluate both direct and moderating relationships. The findings reveal that CSR does not significantly influence stock returns, indicating that CSR disclosure has not yet become a dominant factor considered by investors in evaluating stock performance during the observed period. Conversely, asset effectiveness shows a positive and significant effect on stock returns, suggesting that efficient management of company assets can enhance financial performance and strengthen investor confidence. Additionally, dividend policy is proven to moderate the relationship between CSR and asset effectiveness on stock returns, where consistent dividend distribution reinforces the impact of internal company performance on stock performance and provides a positive signal regarding financial stability and future prospects. These results emphasize the importance of optimizing asset utilization and maintaining stable dividend policies to increase investor trust, strengthen company credibility, and improve stock performance in the capital market, particularly in energy sector companies in Indonesia.